A new species of Truljalia Gorochov 1985 from Taiwan (Orthoptera: Gryllidae; Podoscirtinae; Podoscirtini) - He, Zhuqing (Zootaxa, 2012)
A new species, Truljalia formosa sp. nov., is described and illustrated from Dahan Mountain, Pingdong County, Taiwan. All type specimens are deposited in Shanghai Entomological Museum (IEAS).